Nonlinear Integral Sliding Mode Control for a Second Order Nonlinear System - Xie Zheng; Xie Jian; Du Wenzheng; Cheng Hongjie (Journal of Control Science and Engineering)
A nonlinear integral sliding-mode control (NISMC) scheme is proposed for second order nonlinear systems. The new control scheme is characterized by a nonlinear integral sliding manifold which inherits the desired properties of the integral sliding manifold, such as robustness to system external disturbance. In particular, compared with four kinds of sliding mode control (SMC), the proposed control scheme is able to provide better transient performances. Furthermore, the proposed scheme ensures the zero steady-state error in the presence of a constant disturbance or an asymptotically constant disturbance is proved by Lyapunov stability theory and LaSalle invariance principle. Finally, both the theoretical analysis and simulation examples demonstrate the validity of the proposed scheme.